PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KOTA AMBON - Sherly Ferdinandus (Jurnal Cita Ekonomika, 2020)
The research aims to a) analyze the effect of Government Expenditure in the form of direct expenditure on Economic Growth in Ambon City, b) analyze the effect of Government Expenditures in the form of indirect expenditure on Economic Growth in Ambon City. The study was conducted at the Ambon Central Statistics Bureau by using secondary data, namely GRDP at 2000 Constant Prices, in 2009-2018. The analytical method used is multiple linear regression using eviews 6.0. The results are: a) Direct spending contributes positively and significantly to economic growth in Ambon City with a significance level of 5% or a confidence level of 95%; b) Indirect Expenditures contribute positively and significantly to economic growth in Ambon City with a significance level of 5% or a confidence level of 95%; c) Direct Spending and Indirect Spending together contribute positively and significantly to economic growth in Ambon City with a significance level of 5% or a confidence level of 95% with a coefficient of determination (R2) of 96.44%